2016
DOI: 10.15436/2381-0750.16.1228
|View full text |Cite
|
Sign up to set email alerts
|

New Record of The tassled Scorpion Fish, Scorpaenopsis Oxycephala (bleeker, 1849) (Order: Scorpaeniformes, Family: Scorpaenidae) From Visakhapatnam Coast, Indian Waters

Abstract: Based on twenty two specimens of the Tassled Scorpion Fish, species of Scorpaenopsis oxycephala (Bleeker, 1849) (85-96 mm, TL) collected from the Visakhapatnam coastal waters, east coast of India, we described Scorpaenopsis oxycephala as the new record from Indian Ichthyofauna.This species mainly characterized by having 12 dorsal spines, preopercular with five spines; supraorbital tentacle long; scales present in the space between opercular spines naked; occipital very shallow; pectoral length 26.22 in percent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…In India, pugnose ponyfish (Secutor sp.) is one of the major by-catch composition (Muddula 2015) from the country leiognathids were known 16 species (Abraham et al 2011).…”
Section: Fish Biodiversitymentioning
confidence: 99%
“…In India, pugnose ponyfish (Secutor sp.) is one of the major by-catch composition (Muddula 2015) from the country leiognathids were known 16 species (Abraham et al 2011).…”
Section: Fish Biodiversitymentioning
confidence: 99%
“…Wantiez and Kulbicki (1995) found leiognathids of soft bottom communities were the major species in density and biomass like L. rivulatus and S. ruconius. In India, pugnose ponyfish (Secutor sp) is one of the major by-catch composition (Muddula 2015) from the country leiognathids were known 16 species (Abraham et al 2011), in Sri Lanka 13 species , in Malaysia 22 species (Seah et al 2011) that were identified from eight or nine genera (Seah et al 2012), at certain location of Malaysia such as the coastal waters of Pulau Sibu-Tinggi nine species (Mazlan et al 2006), and in Thailand found in intertidal mudflats seven species (Sichum and Tantichodok 2013). In Indonesia, these fishes from various places were reported 11 species (Suyatna et al 2010), 10 species (Wedjatmiko 2007), 20 species (Pauly 1977.…”
Section: Physical and Chemical Propertiesmentioning
confidence: 99%